2021
DOI: 10.28940/terra.v39i0.544
|View full text |Cite
|
Sign up to set email alerts
|

Valor económico del agua en el Distrito de Riego 100, Alfajayucan, Hidalgo

Abstract: El agua para consumo humano se distribuye entre los f ines que la demandan: doméstico, agropecuario e industrial. De acuerdo a lo reportado por la FAO y UNESCO la agricultura consume 69%, el consumo doméstico utiliza 10% y la industria el 21%. Dada la importancia del agua en la agricultura se requiere conocer la asignación óptima del recurso dado un patrón de cultivos, así como el valor económico del líquido. El objetivo de este trabajo fue el obtener un patrón óptimo de cultivos en el Distrito de Riego (DR) 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The results showed that the water shadow price of the base model was MN$3.9 m 3 ; this price is much higher than the price paid by the users (MN$0.15 m 3 ). A similar relation was found by Martínez-Luna et al (2021), who recorded a MN$1.44 m 3 price for the Irrigation District 100, in Alfajayucan, Hidalgo, Mexico. That price is higher than the irrigation fees paid by the producers (MN$0.02 m 3 ).…”
Section: Resultssupporting
confidence: 82%
“…The results showed that the water shadow price of the base model was MN$3.9 m 3 ; this price is much higher than the price paid by the users (MN$0.15 m 3 ). A similar relation was found by Martínez-Luna et al (2021), who recorded a MN$1.44 m 3 price for the Irrigation District 100, in Alfajayucan, Hidalgo, Mexico. That price is higher than the irrigation fees paid by the producers (MN$0.02 m 3 ).…”
Section: Resultssupporting
confidence: 82%
“…Irrigated agriculture consumes globally 69% of the useful water available (Martínez et al, 2021). The use of technology to elevate the efficiency of water in the agricultural sector acquires increasingly more relevance, with actions in the various stages of their cycle.…”
Section: Introductionmentioning
confidence: 99%